Use of Enriched Mine Water to Grow the Cyanobacterium Arthrospira platensis in Photobioreactors - Massimo Milia; Valeria Andreotti; Angelica Giglioli; Viviana Pasquini; Pierantonio Addis; Alberto Angioni (Foods)
The demand for sustainable and high-nutritional food sources is forcing the industrial sector to find alternatives to animal proteins. Microalgae and macroalgae showed remarkable protein and bioactive compound content, offering a promising solution for the food industry. However, the high production cost represents the main concern related to microalgae development. Thus, strategies that can reduce production costs, preserve the environment, and improve the nutritional characteristics of microalgae are required. Exploiting water from dismissed mines could lead to energy savings in production by opening new industrial opportunities to produce microalgae. Arthrospira platensis (Spirulina) can be grown in open ponds and photobioreactors; the composition of the growth medium and the light radiation could affect its biochemical composition. This work investigated the influence of mine water with the addition of Zarrouk growth medium on the biochemical composition of the final dried Spirulina. The trials were performed in vertical tubular photobioreactors (PBRs) exposed to the same light radiance. Samples were compared with standard growing conditions using distilled water with the addition of Zarrouk medium. Spirulina strains showed good tolerance to medium/high concentrations of Cl−, SO42− and nitrogen in mine water. The experiment lasted 12 days, showing significant differences in protein, lipids, and carbohydrates between trials. Spirulina grown in mine water showed higher protein levels, 52.64 ± 2.51 g·100 g−1 dry weight. On the other hand, Spirulina grown in distilled water had higher lipids and carbohydrate levels, accounting for 9.22 ± 1.01 and 31.72 ± 1.57 g·100 g−1 dry weight. At the end of the experiment, both trials showed similar growth and pigment concentration. The availability of a high amount of mine water at no cost and at the ideal temperature for Spirulina cultivation increases environmental sustainability and reduces production costs. The results in terms of biomass were comparable to those of standard cultivation, whereas proteins showed higher values. Moreover, coupling renewable energy sources can further reduce production costs, with promising industrial and market developments.